Implementasi Bagi Hasil dalam Perspektif Balanced Scorecard di Restoran 'The Stone' Batee Iliek Bireuen Aceh - Amsal, Daniel (Ameena Journal, 2024)
Currently, performance evaluation at "The Stone" restaurant is primarily focused on financial metrics. To address this limitation, adopting the Balanced Scorecard with four perspectives (financial, customer, internal business, and learning and growth) offers a more comprehensive approach. The research methodology employs a qualitative approach involving analysis of internal documents, literature review, and observational studies. The implementation of profit-sharing in the restaurant divides profits equally between managers and owners, with performance results showing increased sales in line with agreed-upon targets. Evaluation from the customer perspective indicates improved satisfaction with the restaurant's products and services. The internal business perspective highlights product innovation, operational processes, and after-sales service. Meanwhile, the learning and growth perspective measures employee satisfaction, information system capabilities, and the impact of motivation on performance. The implications of applying the Balanced Scorecard on restaurant performance are evident in increased ROI and enhanced customer perception, along with higher revenue and employee morale.